Implementasi Sistem Informasi Manajemen Dalam Penggunaan PLN Mobile UP3 Binjai Untuk Meningkatkan Efisiensi Pelayanan Pelanggan - Natria Aminarti; Rayyan Firdaus (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
PT PLN (Persero) UP3 Binjai is one of the PLN units that supply electricity to the community. Digital services launched by PLN in the form of PLN Mobile continue to be developed to meet customer needs and satisfaction as well as ease of access. The purpose of this study was to determine the development of efficient customer service through the use of PLN Mobile in UP3 Binjai. The literature review method is used to collect research data by using literature studies to collect materials from books and scientific journals regarding the use of PLN Mobile. From the results of the study, the PLN Mobile application provides benefits for the UP3 Binjai community to find solutions to customer electricity problems, ranging from applying for new electricity installations, checking bills, switching power, responding to complaints and power outages, to purchasing electricity tokens. However, there is a weakness, namely when customers check their bills, customers cannot see information on how much Rupiah is charged, only the month billed. This PLN Mobile application will also have a positive impact on customers and PLN employees because it is more efficient and saves time and energy for customers and employees in resolving customer complaints.